2018
DOI: 10.2967/jnumed.117.206730
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SPECT Tracer to Image c-Met Expression in a Xenograft Model of Non–Small Cell Lung Cancer

Abstract: Elevated expression of the c-Met receptor plays a crucial role in cancers. In non-small cell lung cancer (NSCLC), aberrant activation of the c-Met signaling pathway contributes to tumorigenesis and cancer progression and may mediate acquired resistance to epidermal growth factor receptor-targeted therapy. c-Met is therefore emerging as a promising therapeutic target for NSCLC, and methods for noninvasive in vivo assessment of c-Met expression would improve NSCLC treatment and diagnosis. We developed a new c-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…17 Molecular imaging of c-MET expression has the potential to support the clinical evaluation of MET-targeted therapies by assisting in patient selection and in monitoring drug efficacy. [18][19][20] MetMAb (onartuzumab, Genentech Inc., South San Francisco, CA) contains a humanized one-armed monovalent anti-MET antibody designed to bind the extracellular domain of c-MET and thereby block activation by HGF. 21,22 MetMAb has been investigated in phase III trials as a treatment for non-small-cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…17 Molecular imaging of c-MET expression has the potential to support the clinical evaluation of MET-targeted therapies by assisting in patient selection and in monitoring drug efficacy. [18][19][20] MetMAb (onartuzumab, Genentech Inc., South San Francisco, CA) contains a humanized one-armed monovalent anti-MET antibody designed to bind the extracellular domain of c-MET and thereby block activation by HGF. 21,22 MetMAb has been investigated in phase III trials as a treatment for non-small-cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies have inherent limitations including large size, weak tissue penetration, prolonged clearance, and potential immunogenicity. Compared with antibodies, low molecular weight peptides’ molecular imaging agents present some advantages such as favorable pharmacokinetic and tissue distribution patterns, higher permeability, lower toxicity, less immunogenicity, and easy accessibility for chemical modification (Han et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have shown that the expression level and activation status of MET are closely correlated to MET-targeted therapy response and clinical prognosis, thus highlighting the importance of evaluating the MET status during and prior to targeted therapy [ 27 , 281 ]. Due to a limited number of validated MET mAbs that work in formalin-fixed and paraffin embedded biopsy samples, immunohistochemical evaluation of MET expression is a challenge [ 282 ].…”
Section: Receptor Tyrosine Kinase Inhibitors (Rtkis) For Gb Therapymentioning
confidence: 99%